Inovasi Pembelajaran Pendidikan Agama Islam melalui E-Learning di SMA Budaya Bandar Lampung - Nur Asiah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Learning is the totality of learning activity that begins with planning and ending with the evaluation and follow-up. Developments in science followed by the development of internet information technology and leading edge technology. With the innovation of education, the learning process can be developed and improved the quality of the quality of information technology, better known as e-learning. E-learning is a new learning model in the educational use of information technology in teaching and learning. Problems faced by the schools and teachers is the ability to apply e-learning, self-learning culture is lacking, teachers who have not been able to use and develop learning e-learning and Internet network system that can not be accessed. Data collection techniques used in this study was the observation, interview and documentation. Implementation of e-learning often contentious among high schools Cultural Bandar Lampung. In the process of learning in e-learning, an innovation and interaction between learners with learning resources, between teachers and learners. Innovation PAI learning via e-learning can be divided into two namely, a) e-learning is used entirely for learning PAI in SMA Culture Bandar Lampung, b) Learning e-learning at the School of Culture serve as a complement to conventional learning.